The construction and use of electronic apparatus for studying problems of soil and plant nutrition by means of radio-active isotopes of phosphorus and calcium - Marais, Pieter G (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Sc.) -- University of Stellenbosch, 1952.